1994
DOI: 10.1002/jqs.3390090206
|View full text |Cite
|
Sign up to set email alerts
|

Late Weichselian environmental change in southern Sweden and Denmark

Abstract: A synthesis is presented of the environmental and climatic variations that are inferred to have occurred in southern Sweden (up to latitude 59"N) and Denmark during the Weichselian Late-glacial (1 4-9 kaBP). The chronology and characteristics of the main phases of deglaciation, sea-level change, periglacial activity, soil development, vegetation cover and climate change are summarised. A curve representing the main changes in temperature, including quantitative estimates based upon beetle data and using the 'm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 33 publications
8
52
0
Order By: Relevance
“…In addition, we use the rise of Betula (birch) pollen that we regard as a reliable, local correlation horizon. From other studies the Betula rise is found close to the YD-Holocene boundary (Kristiansen et al, 1988;Paus, 1989;Berglund et al, 1994;Bondevik and Mangerud, 2002). In the present study we show that in the Os area, the rise in Betula pollen was slightly delayed compared with the onset of the warming at the YD-Holocene boundary, and a calendar year age estimate for the Betula rise is presented.…”
Section: Introductionsupporting
confidence: 74%
“…In addition, we use the rise of Betula (birch) pollen that we regard as a reliable, local correlation horizon. From other studies the Betula rise is found close to the YD-Holocene boundary (Kristiansen et al, 1988;Paus, 1989;Berglund et al, 1994;Bondevik and Mangerud, 2002). In the present study we show that in the Os area, the rise in Betula pollen was slightly delayed compared with the onset of the warming at the YD-Holocene boundary, and a calendar year age estimate for the Betula rise is presented.…”
Section: Introductionsupporting
confidence: 74%
“…Together with the well-represented Artemisia, Chenopodiaceae and Poaceae, significant similarities with the Late Weichselian steppe/tundra recorded from NW Europe to east of the Urals (e.g. [Berglund 1994]; [Birks 1994]; [Walker 1994]; Melles 1997 and; [Kondratiene 1998]; [Satkunas and Kondratiene 1998]) appear. Along this periglacial belt, macrofossils show that the wind-pollinated Artemisia had some local significance ( [Webb and Moore 1982]; [Kienast 2001]).…”
Section: The Late Weichselianmentioning
confidence: 77%
“…As pointed out by Berglund and Digerfeldt (1970) this may be due to abundant reworking of clay-rich till surrounding the basin. Although unanimous evidence exists of a gradual climatic cooling during late GI-1 in southern Scandinavia (Berglund et al, 1994;Hammarlund and Keen, 1994), the complacent isotopic records obtained on Pisidium within units 1-2 suggest largely constant climatic conditions at this stage. However, the clay gyttja of unit 2 seems to represent a substantial increase in aquatic productivity as reflected by the increased organic carbon content.…”
mentioning
confidence: 85%
“…Given well-documented evidence for a substantial decrease in air temperature (e.g. Berglund et al, 1994) (Dansgaard, 1964), if transferred directly to the lake water, would be opposed by carbonate-water equilibrium effects of ca. −0.25‰°C −1 (Craig, 1965), resulting in a potential sensitivity in the order of +0.45‰°C −1 .…”
mentioning
confidence: 97%